KOORDINASI ANTARA BKKBN PROVINSI LAMPUNG DAN SKPD KABUPATEN/KOTA DALAM PENGELOLAAN PROGRAM KB DI PROVINSI LAMPUNG - Nurmayani, Nurmayani (PRAEVIA, 2011)
The reseach is to study about the coordination between BKKBN lampung province and SKPD regency/city in managing family planning program. The result of research indicates that BKKBN lampung province does the coordination in building and applying the family planning. in this coordination, SKPD regency/city still needs BKKBN lampung province,s support and a help because of limited budget of APBD regency/city.